2017
DOI: 10.1007/s13318-017-0455-5
|View full text |Cite
|
Sign up to set email alerts
|

CYP Suppression in Human Hepatocytes by Monomethyl Auristatin E, the Payload in Brentuximab Vedotin (Adcetris®), is Associated with Microtubule Disruption

Abstract: MMAE was not a CYP inducer in human hepatocytes. However, it caused a concentration-dependent CYP mRNA suppression and activity. The CYP suppression was associated with microtubule disruption, supporting the reports that intact microtubule architecture is required for CYP regulations. The absence of CYP suppression and microtubule disruption in vitro at the clinical plasma concentrations of MMAE (< 10 nM) explains the lack of pharmacokinetic drug interaction between brentuximab vedotin and midazolam, a sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Effect of Abemaciclib on CYP1A2, 2C9, 2D6 and 3A4 Substrates (Wolenski et al, 2018). Despite the numerous examples of CYP downregulation in vitro, there is no clear example of CYP in vitro downregulation translating into meaningful DDIs in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of Abemaciclib on CYP1A2, 2C9, 2D6 and 3A4 Substrates (Wolenski et al, 2018). Despite the numerous examples of CYP downregulation in vitro, there is no clear example of CYP in vitro downregulation translating into meaningful DDIs in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that MMAE exposure was approximately two times higher in patients with severe renal impairment (creatinine clearance < 30 mL/minute; ref. 175). Therefore, it is advisable to avoid the use of Brentuximab vedotin in patients with severe renal dysfunction.…”
Section: Metabolic Profilementioning
confidence: 99%
“…Severe renal impairment with creatinine clearance < 30 mL/min resulted in an increase of MMAE exposure by approximately two-fold. [ 33 ] In a pediatric population, exposures were approximately dose related, with a trend towards lower ADC exposures at lower ages/body weights. Median AUC in children and adolescents was approximately 14% and 3% lower than in adult patients, respectively, while MMAE exposures were 53% lower and 13% higher, respectively [ 34 ].…”
Section: Metabolic Profilementioning
confidence: 99%
“…Strong CYP3A4 and P-gp inhibitors (e.g., ketoconazole, itraconazole, clarithromycin, atazanavir, indinavir, nefazodone, nelfinavir, ritonavir, saquinavir, telithromycin, and voriconazole) were found to increase MMAE exposure by 73% but did not change the plasma exposure to BV. [ 33 ] Co-administration of BV with strong inhibitors may lead to increased incidence of neutropenia. Rifampicin, a strong CYP3A4 inducer, did not alter the plasma exposure to BV but reduced plasma concentrations of MMAE metabolites.…”
Section: Drug Interactionsmentioning
confidence: 99%
See 1 more Smart Citation